Membrane fusion machines of paramyxoviruses: capture of intermediates of fusion - Russell, Charles J. (Oxford University Press, 2001)
Peptides derived from heptad repeat regions adjacent to the fusion peptide and transmembrane domains of many viral fusion proteins form stable helical bundles and inhibit fusion specifically. Paramyxovirus SV5 fusion (F) protein-mediated fusion and its inhibition by the peptides N-1 and C-1 were analyzed. The temperature dependence of fusion by F suggests that thermal energy, destabilizing proline residues and receptor binding by the hemagglutinin–neuraminidase (HN) protein collectively contribute to F activation from a metastable native state. F-mediated fusion was reversibly arrested by low temperature or membrane-incorporated lipids, and the resulting F intermediates were characterized. N-1 inhibited an earlier F intermediate than C-1. Co-expression of HN with F lowered the temperature required to attain the N-1-inhibited intermediate, consistent with HN binding to its receptor stimulating a conformational change in F. C-1 bound and inhibited an intermediate of F that could be detected until a point directly preceding membrane merger. The data are consistent with C-1 binding a pre-hairpin intermediate of F and with helical bundle formation being coupled directly to membrane fusion.